Genomic epidemiology of Campylobacter fetus subsp. venerealis from Germany - Abdel-Glil, Mostafa Y.; Hotzel, Helmut; Tomaso, Herbert; Didelot, Xavier; Brandt, Christian; Seyboldt, Christian; Linde, Jörg; Schwarz, Stefan; Neubauer, Heinrich; El-Adawy, Hosny (Frontiers in Veterinary Science, 2023)
Campylobacter fetus subsp. venerealis (Cfv) causes bovine genital campylobacteriosis (BGC), a World Organization for Animal Health (WOAH)-listed trade-relevant disease characterized by severe reproductive losses, such as infertility, early embryonic death and abortion in cattle. BGC has significant economic implications that have prompted several countries to adopt stringent eradication and surveillance measures to contain the disease. In Germany, there has been a low incidence of BGC cases over the past 28 years. This study aimed to illustrate the genomic diversity of German Cfv strains isolated from different federal states in Germany. This study analyzed 63 Cfv strains, collected between 1985 and 2015, by whole-genome sequencing and compared them with genome data of 91 international Cfv isolates. The phylogenetic analysis showed that the Cfv population is genetically conserved and has geographic clusters. In Germany, one phylogenetic lineage comprising all strains was identified. This German lineage was part of a subclade that probably emerged in the nineteenth century and diversified over time. The results of this study point to a non-recurrent cross-border introduction of Cfv in Germany. The BGC control interventions in Germany can be considered successful as no outbreaks were reported since 2015.